Hanshi Prof. Tatsuo Suzuki visits UiTMCS - Subinon, Rayner (Universiti Teknologi MARA, Sarawak, 2004)
12 January 2004, Monday night was yet another historical event as JPKK WADO-RYU KARATE- DO invited the world's renowned Wado-Ryu Karate-Do master Hanshi Prof Tatsuo Suzuki to our campus to meet all karate members & the students of UiTM. He is also the president of WADO-RYU INTERNATIONAL KARATE FEDERATION (WIKF) which has its branches in Europe, America & Asia. His arrival was most welcome as this was a chance of a lifetime for everyone to meet him in person. He was in Kuching from the 12 to 16 January.